Projections of care for older people with dementia in England: 2015 to 2040. (6th December 2019) - Wittenberg, Raphael; Hu, Bo; Jagger, Carol; Kingston, Andrew; Knapp, Martin; Comas-Herrera, Adelina; King, Derek; Rehill, Amritpal; Banerjee, Sube
Abstract: Background: The number of older people with dementia and the cost of caring for them, already substantial, are expected to rise due to population ageing. Objective: This study makes projections of the number of older people with dementia receiving unpaid care or using care services and associated costs in England. Methods: The study drew on up-to-date information for England from multiple sources including data from the CFASII study, output from the PACSim dynamic microsimulation model, Office for National Statistics population projections and data from the MODEM cohort study. A simulation model was built to make the projections. Results: We project that the number of older people with dementia will more than double in the next 25 years. The number receiving unpaid or formal care is projected to rise by 124%, from 530, 000 in 2015 to 1, 183, 000 in 2040. Total cost of dementia is projected to increase from £23.0 billion in 2015 to £80.1 billion in 2040, and average cost is projected to increase from £35, 100 per person per year in 2015 to £58, 900 per person per year in 2040. Total and average costs of social care are projected to increase much faster than those of healthcare and unpaid care. Conclusion: The numbers of people with dementia and associated costs of care will rise substantially in the coming decades, unless new treatments enable the progression of the condition to be prevented or slowed. Care and support for people with dementia and their family carers will need to be increased.